Retailing in the 21st Century Current and Future Trends - Krafft, Manfred.; Krafft, Manfred.; Mantrala, Murali K.; Mantrala, Murali K. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Retailing in the new millennium stands as an exciting, complex and critical sector of business in most developed as well as emerging economies. Today, the retailing industry is being buffeted by a number of forces simultaneously, e.g., increasing competition within and across retailing formats, the growth of online retailing, the advent of ‘radio frequency identification’ (RFID) technology, the explosion in customer-level data availability, the global expansion of major retail chains like Wal-Mart and METRO Group and so on. Making sense of it all is not easy but of vital importance to retailing practitioners, analysts and policymakers. With crisp and insightful contributions from some of the world’s leading experts in retailing, Retailing in the 21st Century offers in one book a compendium of state-of-the-art, cutting-edge knowledge to guide successful retailing in the new millennium.